Determination of Metal Elements in Red Mud Using Inductively Coupled Plasma-Atomic Emission Spectrometry - Zhao, Wenshan; Liu, Jin; Rao, Zhengyong; Wang, Jing; Zhang, Ling; Li, Deliang (Asian Journal of Chemistry, 2015)
Herein, two kinds of red mud from Sintering and Bayer processes in Henan Branch of Chinese Aluminum Company were characterized quantitatively and qualitatively using the techniques of inductively coupled plasma-atomic emission spectrometry (ICP-AES). Forty six and forty seven kinds of metal elements were found and measured in red mud from Bayer and Sintering process respectively, supporting the recovery value of several metals such as Fe, Ga, Sc and U, etc.